Death of two military pilots in Hawk-108 fighter jet crash - Chng Kay Ly; Mohd Yusmiaidil Putera Mohd Yusof; Ahmad Hafizam Hasmi; Mohd Shah Mahmood (Wolters Kluwer Medknow Publications, 2018)
Deaths associated with emergency seat ejection are rare. This is the first case reported in Malaysia since 1980 involving the death of two renowned fighter pilots postejection as safety measures. Ejection mechanism involves several phases which last for splits of seconds. Each phase has its own setback despite serving as a safety mechanism. Both the pilots' death was as a result of the canopy separation, windblast effect, G-force effect (gravitational force) as well as acceleration effect. High speed and high altitude would have further contributed to the death.